2015
DOI: 10.1007/s40279-015-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Can Exercise Positively Influence the Intervertebral Disc?

Abstract: To better understand what kinds of sports and exercise could be beneficial for the intervertebral disc (IVD), we performed a review to synthesise the literature on IVD adaptation with loading and exercise. The state of the literature did not permit a systematic review; therefore, we performed a narrative review. The majority of the available data come from cell or whole-disc loading models and animal exercise models. However, some studies have examined the impact of specific sports on IVD degeneration in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 100 publications
(108 reference statements)
2
67
1
4
Order By: Relevance
“…In some disciplines, male athletes might tolerate higher loads because of their higher training volume or higher loads during strength training, or because of differences in basic rules (e.g., the number of sets in tennis). Additionally, differences in spinal kinematics have been reported for some disciplines, and a link between spinal kinematics and back pain has been suggested [46]. However, in our investigation, female elite athletes reported a higher prevalence of back pain during the last 3 months and during the last 7 days than did male elite athletes.…”
Section: Discussioncontrasting
confidence: 49%
“…In some disciplines, male athletes might tolerate higher loads because of their higher training volume or higher loads during strength training, or because of differences in basic rules (e.g., the number of sets in tennis). Additionally, differences in spinal kinematics have been reported for some disciplines, and a link between spinal kinematics and back pain has been suggested [46]. However, in our investigation, female elite athletes reported a higher prevalence of back pain during the last 3 months and during the last 7 days than did male elite athletes.…”
Section: Discussioncontrasting
confidence: 49%
“…In the treatment and exercise management of back pain, the focus is often on the muscle system. However, as Belavý et al [61] summarized in a narrative review regarding whether exercise can positively influence the intervertebral discs, the discs are also well-recognized sources of pain. A number of studies summarized by Belavý et al [61] examined intervertebral disc degeneration and/or spinal abnormalities in specific athletic populations, and thoracic and lumbar intervertebral disc or spinal damage is more common in several different types of sports.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Belavý et al [61] summarized in a narrative review regarding whether exercise can positively influence the intervertebral discs, the discs are also well-recognized sources of pain. A number of studies summarized by Belavý et al [61] examined intervertebral disc degeneration and/or spinal abnormalities in specific athletic populations, and thoracic and lumbar intervertebral disc or spinal damage is more common in several different types of sports. As Belavý et al [61] reported, this is seen in sports in which traumatic spinal injury is more frequent (e.g., gymnastics, wrestling), in sports involving repetitive loading of the spine during motion or load extremes (e.g., gymnastics, cricket, weightlifting, rowing), and in sports in which the spine is subject to high-impact loads with sometimes unpredictable landing forces (e.g., horseback riding, volleyball).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic IVD loading of 0.2–0.8 MPa, generating intra-discal pressures of approximately 0.3–1.2 MPa, is thought7 to be an optimal loading magnitude for the IVD. Based upon data on in vivo intradiscal pressures8, activities such as walking and running, but not lifting a 20 kg load or lying down, fall into this loading magnitude window. This corresponds well to our observations here of the impact of exercise in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…These models suggest7 that a “likely anabolic loading window” for the IVD exists: dynamic loading of 0.2–0.8 MPa, generating intra-discal pressures of approximately 0.3–1.2 MPa, at 0.1 to 1 Hz for approximately eight hours a day. Given human data on intra-discal pressures in different activities8, this could9 be extrapolated to suggest that walking or running exercise is likely anabolic for the IVD. Quadrupedal treadmill running exercise in rodents1011 can have a positive impact on the rodent IVD.…”
mentioning
confidence: 99%